Reposisi Strukturalisme, Semantik, Semiotik, dan Hermeneutik Pada Metodologi Tafsir Alquran Dalam Dimensi Filsafat Ilmu - Abu Tamrin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2017)
Abstract:The Koran is the revelation of Allah SWT given to the Prophet Muhammad as a miracle. The study of interpretive methodology is said to be born in Islamic intellectual thought. It is proven after the interpretation has developed, while the new methodology gets the position as the object of study. In the discussion of the style of interpretation and its schools there are eleven groups that interpret the Qur'an. While the interpretation style can be explained in the field: Fiqhy Interpretation (legal style), Philosophical Interpretation (philosophical interpretation), Ilmy Interpretation (scientific interpretation), Tarbawy Interpretation (educational interpretation), Akhlaqi Interpretation (moral interpretation), Tafsir I'tiqady (interpretation of theology) , and interpretation of Sufy (tasawuf interpretation). As for the development of interpretation methodology it can look like; The period of the Prophet Muhammad, the mutaqaddimin period, the final period, and contemporary methods. Some methods of interpretation and style of interpretation: Tafsir al-Tahlili (analytical descriptive), Ijmali interpretation (global interpretation), Muqaran interpretation (comparative interpretation), and interpretation of Maudhu'i. In this paper the Qur'anic interpretation methodology discusses structuralism, semantics, semiotics and hermeneutics. In addition to the final discussion on the methodological study of several commentators, namely: Imam Sufyan al-Tsauri, Imam al-Sulami and Syankani Imam. The paper ends with a closing.Keywords: Method of interpretation, history of development, methodology of interpretation AbstrakAlquran merupakan wahyu Allah Swt yang diberikan kepada Nabi Muhammad sebagai mukjizat. Kajian tentang metodologi tafsir dikatakan baru lahir dalam pemikiran intelektual Islam. Terbukti setelah tafsir mengalami perkembangan, sementara metodologi baru mendapat posisi sebagai objek kajian. Dalam pembahasan corak tafsir dan aliran-alirannya terdapat sebelas golongan yang menafsirkan Alquran. Sedang corak tafsir dapat dijelaskan perbidang: Tafsir Fiqhy (corak hukum), Tafsir Falsafi (tafsir filsafat), Tafsir Ilmy (tafsir ilmiah), Tafsir Tarbawy (tafsir pendidikan), Tafsir Akhlaqi (tafsir akhlak), Tafsir I’tiqady (tafsir teologi), dan Tafsir Sufy (tafsir tasawuf). Akan halnya perkembangan metodologi tafsir dapat terlihat seperti; Periode Nabi Muhammad, periode mutaqaddimin, periode mutaakhirin, dan metode kontemporer. Beberapa metode tafsir dan corak penafsiran: Tafsir al-Tahlili (deskriptif analitis), tafsir Ijmali (tafsir global), tafsir Muqaran (tafsir perbandingan), dan tafsir Maudhu’i. Dalam makalah ini dibahas metodologi tafsir Alquran tentang strukturalisme, semantik, semiotik, dan hermeneutik. Selain pembahasan akhir pada kajian metodologi  beberapa ahli tafsir yaitu: Imam Sufyan al-Tsauri, Imam al-Sulami dan Imam Syankani. Makalah diakhiri dengan penutup.Kata kunci: Metode tafsir, sejarah perkembangan, metodologi tafsir